Portuguese version of Bern illegitimate task scale: validation for the teaching context - Neves, Paula C.; Serrão, Carla; Sousa-Pereira, Fátima; Bessa, Inês Marques; Sarmento, Tatiana; Andrade, Cláudia (Frontiers in Education, 2026)
Illegitimate tasks, though increasingly studied in organizational behavior, remain underexplored in schools, especially among Portuguese teachers. Assessing them is crucial, as they may undermine teachers’ roles, increase stress, and harm well-being and effectiveness. The Bern Illegitimate Tasks Scale (BITS) is a self-report tool assessing perceptions of illegitimate tasks—those needless or unrelated to one’s role—categorized as unreasonable or unnecessary. This study adapted the BITS for Portuguese teachers. The scale showed good factorial validity and internal consistency for both unnecessary and unreasonable task subscales. Confirmatory analysis supported a two-factor model with good fit, and multiple-group analyses confirmed configural metric invariance across teacher samples. Thus, the Portuguese BITS demonstrates solid psychometric properties and is suitable for research with Portuguese teachers.